Analysis of Work Environment, Job Satisfaction and Compensation of Employee Work Quality - Triswanto, Ary; Suswati, Endang; Muda Priyatna, Navi (International Journal Labs, 2024)
This study aims to find out and analyze the influence of the work environment, job satisfaction and compensation on employee work quality. This study uses an explanatory approach with a population of 216 permanent employees at the Mojokerto Head Office. The random sampling technique was used to select a sample of 105 respondents. Data was collected through questionnaires given directly to respondents and analyzed using path analysis. Before the analysis, validity tests, reliability, and classical assumption tests such as multicollinearity, heteroscedasticity, and normality are carried out. The hypothesis was tested with a significance level of ? = 5%. The results of the analysis showed that: a) the work environment had a significant positive effect on job satisfaction, b) compensation had a significant positive effect on job satisfaction, c) the work environment did not have a significant positive effect on work quality, d) compensation had a significant positive effect on work quality, e) job satisfaction had a significant positive effect on work quality, f) the work environment had a significant positive effect on work quality through job satisfaction, and g) compensation has a significant positive effect on job quality through job satisfaction. The results of this study give the implication that company management needs to pay attention to the work environment and compensation as a factor that can increase employee satisfaction and work quality. Increased job satisfaction can contribute directly or indirectly to improving the quality of work, which in turn can affect the overall performance of the organization